2006
DOI: 10.1017/s0031182006001284
|View full text |Cite
|
Sign up to set email alerts
|

The NcGRA7gene encodes the immunodominant 17 kDa antigen ofNeospora caninum

Abstract: A Neospora caninum 17-19 kDa antigenic protein fraction (p17) in one-dimensional polyacrylamide gel electrophoresis (SDS-PAGE) is the immunodominant antigen recognized by sera from bovines naturally infected by N. caninum. To identify the proteins making up the p17 fraction, we screened a new N. caninum tachyzoite cDNA library with an affinity-purified antibody against p17 (APA17). We isolated several cDNA clones with 100% sequence identity to the NcGRA7 gene. This previously described gene encodes a dense gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…The 29-33 and 40-42 kDa proteins corresponded most probably to the two major surface antigens NcSAg1 and NcSRS2, respectively [45]. The 14-22 kDa band had a molecular weight compatible with Gra7 antigen [46]. The heaviest bands (120-138 and 180 kDa) were maybe due to an incomplete protein denaturation.…”
Section: Discussionmentioning
confidence: 93%
“…The 29-33 and 40-42 kDa proteins corresponded most probably to the two major surface antigens NcSAg1 and NcSRS2, respectively [45]. The 14-22 kDa band had a molecular weight compatible with Gra7 antigen [46]. The heaviest bands (120-138 and 180 kDa) were maybe due to an incomplete protein denaturation.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies revealed that NcGRA7 might be involved in the initial host cell invasion process of N. caninum (Augustine et al 1999;Cho et al 2005). NcGRA7 is an immunodominant antigen in both of tachyzoite and bradyzoite stages (Vonlaufen et al 2004;Alvarez-Garcia et al 2007), unlike NcSAG1, which is only expressed in tachyzoites (Fuchs et al 1998) and it seems to be a good marker in detecting antibodies against both stages (Huang et al 2007). The main objective of our study was to clone and express the NcGRA7 gene using an efficient prokaryotic expression vector, in order to produce a sufficient amount of the protein for developing diagnostic kits.…”
Section: Discussionmentioning
confidence: 99%
“…NcROP2 sequence was amplified using as DNA template the pQE30-NcROP2 plasmid (Debache et al, 2008). NcNTPase was amplified from NcLiv cDNA, and NcGRA7 was cloned as previously described (Álvarez-García et al, 2007;Jiménez-Ruiz et al, 2012).…”
Section: Recombinant Protein Cloning and Sequencingmentioning
confidence: 99%
“…coli BL21(DE3)pLysS competent cells (Agilent Technologies) were transformed with the resulting expression vectors and foreign expression of rNcROP40, rNcROP2 and rNcNTPase as a (His) 6 -tagged fusion proteins was carried out following standard procedures (Álvarez-García et al, 2007). Transformed bacteria were cultured in selective medium (Luria Bertoni supplemented with 10 g/l glucose, 100 mg/ml ampicillin and 34 mg/ml chloramphenicol) until the OD 600 reached 0.6.…”
Section: Expression and Purification Of Recombinant Proteinsmentioning
confidence: 99%